The Anatomy and Future of Pakistan's Afghan Interests - Schofield, Julian (Journal of Conflict Studies, 2008)
ABSTRACT The relationship between the nation-building mission in Afghanistan and that country's connection with its influential neighbor Pakistan is very complex. The success of NATO's strategy to strengthen the new Kabul regime depends on its intersection with Pakistani policies. Pakistan's strategy in Afghanistan, in turn, is tied to its broader security policy against India. This is complicated by Afghan-Pakistan disputes over territory, Afghan refusal to recognize the Durand Line as the international border, Pakistan's interdiction of third party trade to and from Afghanistan, and a history of Afghan sponsorship of secessionism in Pakistan. All of these factors contribute to Pakistan's reluctance to contribute to the stabilization of Afghanistan by closing the insurgent sanctuaries in the Federally Administered Tribal Areas. NATO has few non escalatory military options. It has two remaining venues of influence. First, its presence acts as a restraint on Afghan provocation of secessionism, thereby satisfying one of Islamabad's goals. Second, NATO could offer trade and aid incentives to Pakistan to gradually withdraw its support to those elements of its society that foment Pakhtun insurgency in Afghanistan (and Pakistan). The long-term effect of such a strategy would be a gradual economic integration and normalization of the Afghan and Pakistan frontier areas.